2010
DOI: 10.1007/s10344-010-0369-x
|View full text |Cite
|
Sign up to set email alerts
|

Nest box use by woodland dormice (Graphiurus murinus): the influence of life cycle and nest box placement

Abstract: The use of nest boxes by the woodland dormouse, Graphiurus murinus, was investigated over a 13-month period in a riverine forest of the Great Fish River Reserve, South Africa. We predicted that some characteristics of nest box placement would affect nest box use and that the seasonal pattern of nest box use would be linked to the species' life cycle and physiological and socioecological characteristics. Generalized linear models indicated that the time since nest box installation and nest box height above grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…A high rate of use in this study is relative to earlier studies that have commonly reported less than 20% of installed nest boxes being used by mammals. Use has been based on the sum of nest boxes with records over a period of time (Menkhorst ; Lindenmayer et al ; Goldingay et al ; Veiga et al ; Williams et al ) or based on an instantaneous count of records (Madikiza et al ; Warakai et al ). We used both indices (cumulative and instantaneous), because in our rural landscape we conducted three observations in the 2‐year period after nest box installation, whereas, in the urban landscape, nest boxes had been in place for over 3 years, which allowed us to conduct an instantaneous count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high rate of use in this study is relative to earlier studies that have commonly reported less than 20% of installed nest boxes being used by mammals. Use has been based on the sum of nest boxes with records over a period of time (Menkhorst ; Lindenmayer et al ; Goldingay et al ; Veiga et al ; Williams et al ) or based on an instantaneous count of records (Madikiza et al ; Warakai et al ). We used both indices (cumulative and instantaneous), because in our rural landscape we conducted three observations in the 2‐year period after nest box installation, whereas, in the urban landscape, nest boxes had been in place for over 3 years, which allowed us to conduct an instantaneous count.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that insectivorous bat populations can be supported by artificial cavities (Stebbings & Walsh ; Flaquer et al ; Baranauskas ; Bender ). In contrast, evidence for cavity‐dependent non‐flying arboreal mammals is equivocal because non‐flying arboreal mammals may show a relatively low frequency of use of nest boxes (5–8% of boxes, Menkhorst ; 8–23%, Rhind & Bradley ; 8–14%, Lindenmayer et al ; 15%, Durant et al ; 20%, Madikiza et al ; 22%, Franco et al ; 8%, Veiga et al ; 2–12%, Warakai et al ; 13%, Williams et al ). The relative lack of success in attracting some mammal species has led some to conclude that attempts to restore habitat value using artificial cavities may not be successful (Lindenmayer et al ).…”
Section: Introductionmentioning
confidence: 99%
“…A type of activity that is extended all over the world involves hanging up artificial boxes for birds and other animals, e.g., bats, snakes and mammals, that provide a wide range of opportunities for monitoring how animals breed, roost, hibernate, store food, etc. [17–20]. In recent decades, the noninvasive method of camera monitoring in bird houses has allowed animal life to be zoomed to people [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…), roosting (Tyller, Paclík & Remeš ), hibernating (Madikiza et al . ) or food storing (Halonen et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial boxes provide a wide range of opportunities for animal use, including breeding (K€ olliker et al 1998), roosting (Tyller, Pacl ık & Reme s 2012), hibernating (Madikiza et al 2010) or food storing (Halonen et al 2007). In particular, bird species using the boxes to breed allow us to study some of the key topics of evolutionary biology, especially questions about parental care (i.e.…”
Section: Introductionmentioning
confidence: 99%